2012
DOI: 10.1055/s-0031-1298919
|View full text |Cite
|
Sign up to set email alerts
|

Periodisches Fieber, aphthöse Stomatitis, Pharyngitis und Lymphadenitis (PFAPA-Syndrom) im Erwachsenenalter

Abstract: The PFAPA syndrome is an illness that first manifests itself in children. However, it can persist until adulthood or reappear after phases of remission. A knowledge of this periodic fever syndrome and extensive and close cooperation of general practitioners, paediatricians, internists and ENT specialists will be helpful in early diagnosis of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Since the disease is not common, mostly series of case reports have been published in which the effect of surgery has been difficult to demonstrate. However, with randomization and meta-analysis, a positive effect of tonsillectomy has recently been clearly shown [28,29,30]. Of course, tonsillotomy is not suitable for a disease that is probably autoimmune, and the question is whether an adenotonsillectomy is always required to solve the patient's problem.…”
Section: Paradigm Shiftmentioning
confidence: 99%
“…Since the disease is not common, mostly series of case reports have been published in which the effect of surgery has been difficult to demonstrate. However, with randomization and meta-analysis, a positive effect of tonsillectomy has recently been clearly shown [28,29,30]. Of course, tonsillotomy is not suitable for a disease that is probably autoimmune, and the question is whether an adenotonsillectomy is always required to solve the patient's problem.…”
Section: Paradigm Shiftmentioning
confidence: 99%
“…It usually starts before the age of 5 and resolves spontaneously in adolescence. In addition to this classical knowledge, some studies which conducted long-term follow-up of patients diagnosed with PFAPA syndrome in childhood reported that the disease continued for a long time in a small percentage of patients [23,24]. Since the first adult patient with this disease was reported in 2008, many cases of PFAPA syndrome from not only the pediatric age group, but also from the adult age group, have been reported [14,16,[25][26][27][28].…”
Section: Adults Pfapamentioning
confidence: 99%
“…Between febrile episodes, the patients are asymptomatic . The symptoms usually resolve spontaneously before adolescence, but in recent years the syndrome has been described also among adults . The cumulative incidence of PFAPA has been calculated to be about two per 10 000 children up to 5 years of age , making PFAPA the most common periodic childhood febrile syndrome.…”
mentioning
confidence: 99%